Variable temperature study of electro-reduction of 3-nitrophenolate via cyclic and square wave voltammetry: Molecular insights Into electron transfer processes based on the asymmetric Marcus-Hush model - Laborda, E; Suwatchara, D; Rees, N; Henstridge, M; Molina, A; Compton, R (2013)
In this study, variable temperature experiments have been used in conjunction with numerical fitting of cyclic and square wave voltammogram responses via the asymmetric version of Marcus theory to provide molecular insight into the electroreduction of the 3-nitrophenolate anion in DMSO on mercury hemispherical microelectrodes of 23 μm radius. As a result, the reorganization energy, differences between the inner-sphere force constants of the electroactive species, and the degree of adiabaticity have been evaluated. Furthermore, a comparison between the quality of fitting obtained through the Butler-Volmer and asymmetric Marcus-Hush models is also presented to examine the relative ability of the kinetic models in predicting voltammetric responses in a range of temperatures and scan rates. © 2013 Elsevier Ltd. All rights reserved.